Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Get quick and reliable solutions to your questions from a community of experienced professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find all real solutions for the equation [tex]\((6z + 4)^2 - 22 = 0\)[/tex], we will follow these steps:
1. Simplify the Equation:
Start with the given equation:
[tex]\[ (6z + 4)^2 - 22 = 0 \][/tex]
2. Isolate the Square Term:
Add 22 to both sides to isolate the square term:
[tex]\[ (6z + 4)^2 = 22 \][/tex]
3. Take the Square Root:
Take the square root of both sides of the equation:
[tex]\[ 6z + 4 = \pm \sqrt{22} \][/tex]
This results in two separate equations:
[tex]\[ 6z + 4 = \sqrt{22} \quad \text{and} \quad 6z + 4 = -\sqrt{22} \][/tex]
4. Solve for [tex]\(z\)[/tex]:
For the first equation:
[tex]\[ 6z + 4 = \sqrt{22} \][/tex]
Subtract 4 from both sides:
[tex]\[ 6z = \sqrt{22} - 4 \][/tex]
Divide both sides by 6:
[tex]\[ z = \frac{\sqrt{22} - 4}{6} \][/tex]
Simplify the expression:
[tex]\[ z = -\frac{2}{3} + \frac{\sqrt{22}}{6} \][/tex]
For the second equation:
[tex]\[ 6z + 4 = -\sqrt{22} \][/tex]
Subtract 4 from both sides:
[tex]\[ 6z = -\sqrt{22} - 4 \][/tex]
Divide both sides by 6:
[tex]\[ z = \frac{-\sqrt{22} - 4}{6} \][/tex]
Simplify the expression:
[tex]\[ z = -\frac{\sqrt{22}}{6} - \frac{2}{3} \][/tex]
5. List All Real Solutions:
Therefore, the real solutions to the equation [tex]\((6z + 4)^2 - 22 = 0\)[/tex] are:
[tex]\[ z = -\frac{2}{3} + \frac{\sqrt{22}}{6} \][/tex]
and
[tex]\[ z = -\frac{\sqrt{22}}{6} - \frac{2}{3} \][/tex]
These are the solutions to the given quadratic equation.
1. Simplify the Equation:
Start with the given equation:
[tex]\[ (6z + 4)^2 - 22 = 0 \][/tex]
2. Isolate the Square Term:
Add 22 to both sides to isolate the square term:
[tex]\[ (6z + 4)^2 = 22 \][/tex]
3. Take the Square Root:
Take the square root of both sides of the equation:
[tex]\[ 6z + 4 = \pm \sqrt{22} \][/tex]
This results in two separate equations:
[tex]\[ 6z + 4 = \sqrt{22} \quad \text{and} \quad 6z + 4 = -\sqrt{22} \][/tex]
4. Solve for [tex]\(z\)[/tex]:
For the first equation:
[tex]\[ 6z + 4 = \sqrt{22} \][/tex]
Subtract 4 from both sides:
[tex]\[ 6z = \sqrt{22} - 4 \][/tex]
Divide both sides by 6:
[tex]\[ z = \frac{\sqrt{22} - 4}{6} \][/tex]
Simplify the expression:
[tex]\[ z = -\frac{2}{3} + \frac{\sqrt{22}}{6} \][/tex]
For the second equation:
[tex]\[ 6z + 4 = -\sqrt{22} \][/tex]
Subtract 4 from both sides:
[tex]\[ 6z = -\sqrt{22} - 4 \][/tex]
Divide both sides by 6:
[tex]\[ z = \frac{-\sqrt{22} - 4}{6} \][/tex]
Simplify the expression:
[tex]\[ z = -\frac{\sqrt{22}}{6} - \frac{2}{3} \][/tex]
5. List All Real Solutions:
Therefore, the real solutions to the equation [tex]\((6z + 4)^2 - 22 = 0\)[/tex] are:
[tex]\[ z = -\frac{2}{3} + \frac{\sqrt{22}}{6} \][/tex]
and
[tex]\[ z = -\frac{\sqrt{22}}{6} - \frac{2}{3} \][/tex]
These are the solutions to the given quadratic equation.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.